Solid-phase precipitation of CdTe nanoparticles in glass - Yükselici, MH; Allahverdi, Ç (WILEY-V C H VERLAG GMBH, 2003)
Growth of CdTe nanoparticles in glass is studied through the analysis of optical absorption spectroscopy with the help of a quantized state effective mass model. Glass includes nanoparticles with an initial size of similar to1.6 nm on cooling to room temperature from the melt at similar to1000 degreesC. Particles form by heterogeneous nucleation followed by diffusion-limited growth. The narrowest particle size dispersion of 15% is obtained for an average radius of similar to2.28 nm at the end of heat treatment at 600 degreesC for 4.5 h. The magnitude of the absorption related to the number of particles is low due to the oxidation of Te. A combinative use of Ar-rhenius plots and the model yields an activation energy for diffusion of similar to170 kJ mol(-1).
Keywords: SEMICONDUCTOR-DOPED GLASSES; NONLINEAR-OPTICAL PROPERTIES; QUANTUM DOTS; BOROSILICATE GLASS; NANOCRYSTALS; GROWTH; Physics